2011
DOI: 10.1002/qj.763
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric gravity waves revealed in NWP model forecasts

Abstract: Current operational numerical weather prediction models potentially have sufficient spatial and temporal resolution to resolve much of the inertia-gravity wave spectrum (e.g. horizontal wavelengths in the region of 100-1000 km typically, and even longer zonal wavelengths in the Tropics). The effects of gravity wave dynamics are usually considered to be subgrid-scale and parametrizable, either as stationary, mountain waves or travelling, non-orographic waves. Simple techniques for isolating these waves in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 56 publications
5
78
0
Order By: Relevance
“…The ray-tracing technique shows that the wave event is forced by surface winds over mountains reaching heights of 1700 m located over the South American continent. Orographic waves that propagate long distances downstream have also been found in satellite observations (Wu and Jiang, 2002;Wu et al, 2006;Alexander et al, 2008) and in modelling studies (Shutts and Vosper, 2011). In this work, we emphasize the long lateral propagation of the waves (by lateral we mean perpendicular to the downstream direction), which are found to propagate laterally over 1500 km with amplitudes of about 5 m s −1 at those distances.…”
Section: Discussionsupporting
confidence: 62%
“…The ray-tracing technique shows that the wave event is forced by surface winds over mountains reaching heights of 1700 m located over the South American continent. Orographic waves that propagate long distances downstream have also been found in satellite observations (Wu and Jiang, 2002;Wu et al, 2006;Alexander et al, 2008) and in modelling studies (Shutts and Vosper, 2011). In this work, we emphasize the long lateral propagation of the waves (by lateral we mean perpendicular to the downstream direction), which are found to propagate laterally over 1500 km with amplitudes of about 5 m s −1 at those distances.…”
Section: Discussionsupporting
confidence: 62%
“…small-scale Courant number) may be more appropriate (Bartello and Thomas, 1996). Shutts and Vosper (2011) have shown that gravitywave activity in the operational version of the MetUM is in better agreement with observations from the HighResolution Dynamics Limb Sounder (HIRDLS) instrument when the timestep is decreased from 15 min to 2 min. Figure 5 shows the effect of the timestep on the mean relative error, r. In all cases, the qualitative evolution is unchanged.…”
Section: Sensitivity To Small-scale Motionsmentioning
confidence: 79%
“…Shutts and Vosper, 2011) and coarse vertical resolution. In particular, an increase in the predictive skill of forecasts could be obtained from both modelling and assimilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations